Beyond Inclusion: An Empirical Study of Religious Minorities’ Perceptions Towards Idiosyncratic Deals and Workplace Ostracism - Bhatti, Ramish Zafar; Malik, Beenish; Dost, Mir (Pakistan Business Review, 2025)
Fairness in the workplace is a key component of organizational justice. However,  disparities in the granting of Idiosyncratic deals (I-deals) can lead to a perception of injustice  among bystanders. These perceived inequities can trigger negative emotional and behavioral  responses, such as malicious envy and workplace ostracism. This study investigates the  relationship between co-worker perception of other employees’ I-deals and workplace ostracism, with serial mediation considering perceived I-deals differentiation and malicious  envy. Using a quantitative research design, data were collected from 330 employees across  26 departments within the Government of Balochistan, Pakistan. Religious minority groups  were chosen as participants in this study with the perception of purposive and snowball  sampling techniques. Partial Least Squares Structural Equation Modeling (PLS-SEM)  was utilized to test the relationships that were proposed. The findings demonstrate that  perceptions of inequality in the allocation of I-deals ignite the process of social comparisons,  boost an ill feeling of envy, and eventually culminate in ostracism in the workplace. The results emphasize the essence of fair and transparent human resource practices in reducing  these negative organization aspects. Enhancing equity in assigning I-deals enables the  organization to practice inclusiveness at the workplace, which improves the well-being of employees and social cohesion. The study fits the overall discussion on workplace fairness, social exchange processes, and relationships between different groups and other goals, the Sustainable Development Goals (SDGs), namely SDG 10, that are related to inequality reduction, and SDG 16, which promotes peace, justice, and stable institutions.
Keywords: Idiosyncratic deals; perceived I-deals differentiation; malicious envy; workplace ostracism; SDGS